Effect of halotolerant plant growth-promoting rhizobacteria from Bougainvillea glabra on wheat and maize seedlings under NaCl stress - Arun Karnwal (BioTechnologia, 2021)
Wheat and maize are the main staple food crops that contribute to human food security. Their growth, however, is reduced under stresses such as salinity. The plant microbiome is associated with each plant tissue and develops a holobiont in association with the plant. Plants actively manage the configuration of their related bacterial population and its function. These microorganisms provide a broad range of benefits and advantages to the plants. The present study aimed to examine the growth improvement of wheat var. HD 2687 and maize var. PSCL-4642 under salinity at the seedling stage following inoculation of salt-tolerant plant growth-promoting rhizobacteria (PGPR) BoGl120 purified from Bougainvillea glabra. The seed germination potential with/without bacterial inoculation was examined at 50, 100, 150, and 200 mM NaCl concentrations for both crops. Compared to controls, at 50 mM NaCl concentration, the BoGl120 isolate provided the maximum radicle length in maize (32 mm) and in wheat (24.8 mm). At 100 mM NaCl concentration, however, the radicle length of wheat and maize seedlings was decreased. Inoculation of plants with the BoGl120 isolate enhanced the plumule length of seedlings at different NaCl concentrations as compared to controls. In comparison with controls, BoGl120 improved the plumule length of wheat to 32.6, 14.0, and 8 mm at 50, 100, and 150 mM NaCl concentrations, respectively. The results of the present study support the concept that PGPRs could help to increase the tolerance against saline stress in wheat and maize at the seedling stage.